Chances of Multilingualism and Intercultural Communication in Hungary and Austria: Joint Projects (Training and Practice : Journal of Educational Sciences, 2011)
Pluralism and diversity are parts of citizens’ everyday life in Europe. The importance of intercultural communication is unquestionable in the European Union. We still have to ask if we have achieved our common goals concerning education, born in the wake of an euphory following the Pan-European Picnic which opened the Austro-Hungarian border again. A number of educational partneships have been established between the two countries since then, creating common best practices. In our paper we discuss the status of multilingualism in the region, and review the joint efforts as well as successful foreign language focused projects of the Austrian and Hungarian educational policies throughout their cooperation established in 1989.